A General Model of Dynamic Labor Demand - Hamermesh, Daniel S. (The Review of Economics and Statistics, 1992)
This study derives and estimates a dynamic model of factor demand that includes both fixed and quadratic variable costs of adjustment. Using quarterly data on the employment of mechanics at seven airlines, it finds that both types of adjustment costs characterize the dynamic constraints facing employers. Using monthly data covering production-worker employment in seven manufacturing plants, it shows that only fixed costs are important. The apparent diversity of the underlying costs of adjustment means it is difficult to draw useful inferences from macroeconometric estimates. It suggests the importance of examining broader arrays of microeconomic time series describing labor demand.